Analisis Karya Musique Concrete: The Genesis Chapter One - Margaretha Christie Setiana; I Gde Made Indra Sadguna; I Wayan Sudirana (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2024)
Purpose: Musique concrete creation ‘The Genesis Chapter One’ explores the theme of the creation of the universe based on the Bible in Genesis 1:1-31. This composition encompasses natural soundscapes as sound sources and presenting the work in spatial audio. This project aims to articulate the aesthetics of musique concrete as a reference for future creations and to explore how communication is established with the audience through spatial audio techniques. Unlike conventional musique concrete, this work assigns meaning to each medium used and presents it in a spatial audio format. Methods:The creation process is guided by theories of musique concrete and Roland Barthes' semiotics, using a method developed from Alma M. Hawkins' approach, which includes three stages: pre-production (exploration and improvisation), production (forming), and post-production (recording). Results and Discussion: The mediums used include soundscape sampling, synthesizers, human vocals, and drums, with live presentation utilizing spatial surround 6.1. Conclusion: The work is divided into three parts: Part I depicts the state before creation, Part II focuses on the growth of the universe with rhythm, and Part III is inspired by the human heartbeat, symbolizing life and its correlation with the universe.